Gestation in times of COVID-19 pandemic. Hospital Nacional Docente Madre Niño San Bartolomé, Lima, Peru - Vera Loyola, Edy Martin (2020)
Introduction: COVID-19 and pregnancy is a new intercurrence in risk assessment for the care of the pregnant woman. Since the beginning of the pandemic in the country, cases have been increasing. The first case attended at the San Bartolomé Hospital was on April 12. Since the first reports of COVID+ pregnant women in China, to date, there is more important information on epidemiology and perinatal results for the management of the COVID+ pregnant woman. Objective: To determine the epidemiology and maternal perinatal outcomes of COVID-19 in pregnant women at the Hospital Nacional Docente Madre Niño San Bartolomé, Lima, Peru. Methods: Observational cross-sectional study, from April to July 2020. All the pregnant women who arrived at the obstetric emergency at Hospital San Bartolomé were included, and they underwent an immunochromatography test for IgM / IgG, to determine the seroprevalence of COVID-19. Obstetric and perinatal variables were collected in a data sheet upon admission to the emergency room. Results: Rapid test for SARS-CoV-19 was performed in 345 pregnant women who were hospitalized for delivery care. The average age was 27 years, with 10% adolescents and 16% over 35 years; 60% had 2 to 4 pregnancies, 38% of deliveries were vaginal, 15% of them preterm; 1.2% of the pregnant women were symptomatic and 0.2% were admitted to the intensive care unit. 61% of the newborns weighed between 2 500 and 3 500 g, 53% were male, 94% had an Apgar score greater than 7 at one minute, 3.3% with a positive swab within the first 24 hours. There were 3% fetal deaths. 48% of the pregnant women came from the Northern Cone of the city of Lima. Conclusions: Almost 100% of the pregnant women were asymptomatic and only 0.2% had respiratory complications. The mode of delivery by cesarean section was low in relation to other publications, all had obstetric indication. A small number of neonates had a positive swab. There was a higher incidence of fetal deaths in July 2020. The highest percentage of patients came from the Northern Cone of Lima.